2014
DOI: 10.3389/fphy.2014.00031
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth dopant (Nd, Gd, Dy, and Er) hybridization in lithium tetraborate

Abstract: The four dopants (Nd, Gd, Dy, and Er) substitutionally occupy the Li + sites in lithium tetraborate (Li 2 B 4 O 7 : RE) glasses as determined by analysis of the extended X-ray absorption fine structure. The dopants are coordinated by 6-8 oxygen at a distance of 2.3 to 2.5 Å, depending on the rare earth. The inverse relationship between the RE-O coordination distance and rare earth (RE) atomic number is consistent with the expected lanthanide atomic radial contraction with increased atomic number. Through analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 82 publications
4
35
0
Order By: Relevance
“…Basing on the presented above structural data for borate glasses and their crystalline analogues [48,[70][71][72][73][74][75] as well as results of MAS NMR [71] and EXAFS investigations [76,77] The proposed local structure of the Sm 3+ luminescence centres in the investigated borate glasses well correlates with the obtained in this work spectroscopic data, particularly with the luminescence lifetimes, which are very sensitive to the local environments. As seen from Table 2 …”
Section: The Local Structure Of Sm 3+ Luminescence Centres In the Borsupporting
confidence: 70%
See 1 more Smart Citation
“…Basing on the presented above structural data for borate glasses and their crystalline analogues [48,[70][71][72][73][74][75] as well as results of MAS NMR [71] and EXAFS investigations [76,77] The proposed local structure of the Sm 3+ luminescence centres in the investigated borate glasses well correlates with the obtained in this work spectroscopic data, particularly with the luminescence lifetimes, which are very sensitive to the local environments. As seen from Table 2 …”
Section: The Local Structure Of Sm 3+ Luminescence Centres In the Borsupporting
confidence: 70%
“…This consideration based on direct EXAFS (Extended X-ray Absorption Fine Structure) studies of the rare-earth impurity ions, according which in [76,77] it was shown that the local structure (the first coordination shells) of the rare-earth ions are closely similar in oxide glasses and crystals with the same chemical composition. Furthermore, the magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy [71] confirms the similarity of local structure of the cationic sites in borate glasses and crystals with the same chemical composition.…”
Section: The Local Structure Of Sm 3+ Luminescence Centres In the Bormentioning
confidence: 99%
“…Although significant experimental work has been done to study the effect of Ln‐dopants in some ceramic systems, Al 2 O 3 has not been well explored . Computational studies at the level of first principles theory on Al 2 O 3 have focused on transition metal (TM) and metalloid‐induced phase stability .…”
Section: Introductionmentioning
confidence: 99%
“…UO 2 supports extra O in interstitial sites readily (hence the rapid formation of UO 2+ x on UO 2 surfaces and the growth of UO 2 –U 4 O 9 solid‐solutions), which is made possible by the many valence states available to U compared to Th. The density of states for the 5f occupation in UO 2 is much greater than in ThO 2 , where recent calculations and experimentation show only partial occupancy . However, it is this nature of ThO 2 which might assist stabilization of the U valence in mixed oxides, even in the event of O interstitials (say induced from radiation events) that would be important, particularly to the nuclear power industry and mixed oxide fuels.…”
Section: Resultsmentioning
confidence: 99%
“…In previous EXAFS analyses that fit theoretical models to experimental data, the analysis was difficult and time‐exhaustive, taking weeks if not months . Some difficulties included confirming false minima in the fitting parameter spaces and avoiding experimenter bias in parameter adjustment.…”
Section: Methodsmentioning
confidence: 99%